New far-field extrapolation method for the computation of electric fields - Yang, Xin (Oficyna Wydawnicza Politechniki Wrocławskiej, 2021)
The extrapolation of the electric field is studied theoretically both in frequency domain and time domain. Combining Gauss’s law with the approximation method in engineering, two new formulas for the scattering field calculation are derived from different logical ideas based on Stratton–Chu formula. The consistency property of the derived formulas is investigated, and the third formula for the scattering field calculation is further obtained. Finally, the time-domain extrapolation is discussed based on the formulas, followed by a simple numerical example. The results obtained are characterized by a simple form and intuitive physical meaning, and are helpful to calculate certain engineering problems.
Optica Applicata, Vol. 51, 2021, nr 3, s. 321-333
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; far-field extrapolation; Stratton–Chu formula; Gauss’s law; prawo Gaussa